Language learning strategies in EFL used by athlete students in sport language center - Tomy Suhaili Rozaq; Waode Hamsia; Linda Mayasari (Concept : Community Concern for English Pedagogy and Teaching, 2021)
The aim of this research is to identify the type of English learning strategies as foreign language used by athlete students and to analyse on how to use language learning strategies in learning English as foreign language to their achievement in English speaking skill. This research was conducted on six athlete students in Sport Language Center of Surabaya who are able to speak English in International Competition. The data for this research were taken from observation and filling up questionnaire analysis. It can be concluded that language learning strategies in learning English as foreign language for the students were very useful and helpful. The learning strategies are believed to be responsible for successful language acquisition and significant in language learning. Thus, in learning English as a foreign language, appropriate language learning strategies were significant. Athlete students who are swimmers in Sport Language Center needed to know how to learn, and swimmer coach needed to know how to facilitate his process in teaching English. Hopefully this research can also inspire other researcher who are interested in conducting research on other aspects of language learning strategies. Keywords: Language Learning Strategy; Athlete; English as foreign language